Pressure retaining method based on phase change for coring of gas hydrate-bearing sediments in offshore drilling. (25th August 2016) - Li, Lijia; Peng, Jianming; Gao, Qing; Sun, Mingze; Liu, Yan; Li, Ming; Chen, Baoyi; Bo, Kun
Highlights: Pressure corer based on phase-changing of situ drilling fluid has been proposed. Ice valve made from seawater mixed with 7% bentonite can sustain pressure up to 47 MPa. Long length and lower freezing temperature can improve ice valve pressure sustaining. Abstract: Coring of gas hydrate-bearing sediment with situ-pressure retained is significant for both geophysics and geochemistry. However, the core recovery of current pressure corers is relatively low, which is attributed to the sensitivity of mechanical valves to solid particles and drilling cuttings. To improve the core recovery of the pressure corers, the pressure retaining method based on the phase change of situ drilling fluid has been used to seal the core tube mouth. The pressure retaining capacity of the ice valves made from seawater mixed with different mass concentrations of bentonite was tested; the influence of the ice valve length and freezing temperature on the pressure retaining capacity was also studied. Results show that the ice valve made from pure seawater could not retain pressure for the fissures caused by stress because of the temperature difference and the incompletely freezing of the ice valve caused by the concentrated inorganic salts in the core of the ice valve. The ice valve made from seawater mixed with 7% mass concentration of bentonite can sustain pressures of up to 47 MPa. Both high ice valve length and low freezing temperature are beneficial for improving the pressure sustaining capacity of the ice valve. Results indicate that using the ice valve made from seawater mixed with bentonite to instead mechanical valves in the pressure corer can be a potential solution to improve the recovery of pressurized hydrate-bearing sediment core.